2022
DOI: 10.1155/2022/5239479
|View full text |Cite|
|
Sign up to set email alerts
|

Application of 3D Digital Image Processing Technology in Modern Packaging Design

Abstract: In this paper, a modern packaging model is constructed by combining three-dimensional digital image processing technology, which has achieved the effect of improving the quality of modern packaging design. In addition, this paper proposes a new target recognition and tracking scheme, which uses the method of servo motor to control the synchronous conveyor belt to monitor the moving objects in real time and proposes a decision analysis algorithm to avoid repeated identification of multiple moving targets. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Meng and others found that, in recent years, with the rapid development of China's industrial economy, the improvement of people's quality of life, and the enhancement of environmental protection awareness, paper packaging has become the most potential green packaging form because of its wide source of raw materials, easy molding, degradable recycling, and other advantages [4]. According to the literature, the output value of corrugated paper industry in Sichuan has surpassed that of the packaging industry in Europe since 1999.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Meng and others found that, in recent years, with the rapid development of China's industrial economy, the improvement of people's quality of life, and the enhancement of environmental protection awareness, paper packaging has become the most potential green packaging form because of its wide source of raw materials, easy molding, degradable recycling, and other advantages [4]. According to the literature, the output value of corrugated paper industry in Sichuan has surpassed that of the packaging industry in Europe since 1999.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, it refers to the degree of standardized design and manufacturing adopted. (4) Economy: it mainly refers to whether the comparison between the cost of packaging and the value of content is reasonable. (5) Realizability: it refers to whether the packaging materials are easy to obtain, whether the packaging structure is feasible, whether the whole packaging is suitable for mechanized and automatic production, etc.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the rapid development of digital technology not only influences people's lifestyles, but also gives rise to many new media, and to a certain extent, influences and changes the design mode [1][2][3]. The connotations and extensions of visual communication design are gradually enhanced in the context of constantly updating and changing media [4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The visual genetic decoding process of graphic digital designThrough on-site digital photography, scanning, extraction and other methods, using the digital era platform, through computer graphics and digital image processing methods, focusing on the technological processing, splitting and extraction of color genes. This paper takes Dunhuang mural as the research object to carry out the construction of digital design visual gene decoding model[25], as shown in Figure2. As shown in Figure2, Dunhuang mural input, first through image preprocessing and layer processing, using clustering methods to analyze and extract the main color set data set and tonal color data set, for local color, title color and successive generations of color and other issues, to obtain the color data set, to obtain the complete data set.…”
mentioning
confidence: 99%